Tailoring the HHx monomer content of P(HB-co-HHx) by flexible substrate compositions: scale-up from deep-well-plates to laboratory bioreactor cultivations - Santolin, Lara; Thiele, Isabel; Neubauer, Peter; Riedel, Sebastian L. (Frontiers in Bioengineering and Biotechnology, 2023)
The enhanced material properties of the microbially synthetized polyhydroxyalkanoate (PHA) copolymer poly(hydroxybutyrate-co-hydroxyhexanoate) [P(HB-co-HHx)] show that this naturally biodegradable biopolymer could replace various functionalities of established petrochemical plastics. In fact, the thermal processability, toughness and degradation rate of P(HB-co-HHx) can be tuned by modulating the molar fraction of HHx in the copolymer, allowing the production of à-la-carte polymers. We have developed a simple batch strategy to precisely control the HHx content of P(HB-co-HHx) to obtain tailor-made PHAs with defined properties. By adjusting the ratio of fructose to canola oil as substrates for the cultivation of recombinant Ralstonia eutropha Re2058/pCB113, the molar fraction of HHx in P(HB-co-HHx) could be adjusted within a range of 2 – 17 mol% without compromising polymer yields. The chosen strategy proved to be robust from the mL-scale in deep-well-plates to 1-L batch bioreactor cultivations.